Assessment of oxidative status and genotoxicity in photocopier operators: a pilot study - Kleinsorge, Elisa (2011)
Occupational exposure to photocopiers has been indicated as being responsible for a number of health complaints, particularly effects on the respiratory, immunological, and nervous systems. In this study, we investigated oxidative and genotoxic damage in photocopier operators by assessing catalase activity (CAT), reduced vs. oxidized glutathione ratio (GSH/GSSG), level of lipid peroxidation (TBARS), damage index by Comet assay (DICA), and buccal cells with micronuclei (BCMN). Our results reveal that the TBARS levels in operators were increased (27%; p<0.05) but that no significant alterations to GSH/GSSG or CAT activity were observed. The DICA and the number of BCMN were significantly increased (134% and 100%, respectively; p<0.05) in the exposed group. There was a significant association between the time in months spent at work and DNA damage in lymphocytes (rs=0.720; p<0.001) and buccal cell with MN (rs=0.538; p<0.001). Because laser printers and photocopiers have become increasingly used, it is important to control human exposure using reliable biomarkers.